Trapping of submicron and micron-sized particles using innovative induced-charge electrokinetic flow - Zhao, C. (2018)
Microfluidic manipulation of particulate matters has found its applications in cell handling, virus detection, biomolecule concentration and colloidal particle assembly etc. In the literature, optical tweezing, electrophoresis, and dielectrophoresis are well-established techniques for particle manipulations, but these techniques have their respective limitations such as low throughput and high costs for optical tweezing, charged particles required for electrophoresis, complex electrode design for dielectrophoresis. Induced charge electrokinetic (ICEK) flows belong to a new class of flows. One of the basic features for ICEK is the generation of vortices over polarisable surfaces. In literature, these kind of nonlinear vortical flows naturally lend themselves to the mixing enhancement in microfluidic devices. Other than the microfluidic mixing, the applications of induced-charge electrokinetics in microfluidics are very rare. Here a novel and high-throughput technique relying on the induced-charge electrokinetics is proposed and demonstrated for simultaneous trapping and concentration of submicron- to micron-sized particles. The fabricated microfluidic device is simply composed of a straight channel and a gold patch on the bottom wall of channel. Under DC-biased AC electric driving voltages, the trapping of particles over the edge of the conducting gold patch are achieved. Moreover, systematic studies are conducted to investigate the effects AC frequency, AC amplitude, DC offset and particle size on the performance of trapping and concentration by ICEK. In addition, a numerical model is developed to explain the underlying mechanisms of particle trapping via ICEK.